Bispecific Antibody Therapy for Effective Cardiac Repair through Redirection of Endogenous Stem Cells. Issue 10 (31st May 2019) - Huang, Ke; Li, Zhenhua; Su, Teng; Shen, Deliang; Hu, Shiqi; Cheng, Ke
Abstract: Bone marrow stem cells (BMSCs) are a promising strategy for cardiac regenerative therapy for myocardial infarction (MI). However, cell transplantation has to overcome a number of hurdles, such as cell quality control, clinical practicality, low cell retention/engraftment, and immune reactions when allogeneic cells are used. Bispecific antibodies (BsAbs) have been developed as potential agents in cancer immunotherapy but their application is sparse in cardiovascular diseases. In the present study, BsAbs are designed by chemical cycloaddition of F(ab′)2 fragments from monoclonal anti‐CD34 and anti‐ cardiac myosin heavy chain (CMHC) antibodies, which specifically targets circulating CD34‐positive cells and injured cardiomyocytes simultaneously. It is hypothesized that intravenous administration of stem cell re‐directing (SCRD) BsAbs (anti‐CD34‐F(ab′)2 –anti‐CMHC‐F(ab′)2 ) can home endogenous BMSCs to the injured heart for cardiac repair. The in vivo studies in a mouse model with heart ischemia/reperfusion (I/R) injury demonstrate the safety and therapeutic potency of SCRD BsAb, which supports cardiac recovery by reducing scarring, promoting angiomyogenesis, and boosting cardiac function. Abstract : A stem cell re‐directing (SCRD) bispecific antibody (BsAb) is designed to effectively recruit endogenous stem cells to treat myocardial infarction using an intravenous delivery approach. SCRD BsAb specifically targets mobilized bone marrow stem cells and injured cardiomyocytes, and conjoins the two for effective cardiac repair.